HEC Digital Library: online information resources and its importance for the faculty of Universities of Balochistan - Baqi, Abdul; Ahmed, Munir (Journal of Quranic and Social Studies, 2022)
This paper is an endeavor to examine the importance of data assets of HEC digital library by faculty members in universities of Balochistan both public and private sectors. The emergence of new technology is a prime source of motivation for users in every field of life. Being prerequisite of modern era, the traditional libraries are also diverting themselves towards digitization. In this scenario the importance and usage of digital library is attaining much attention. Being quantitative in nature the study used questionnaire as part of survey method to collect data from faculty members of Universities of Balochistan. Through this study it became clear that there is lack of digital libraries in Universities of Balochistan. However, some of Universities in Balochistan has established digital portions within the libraries, whereas in many higher institutions of Balochistan the digital libraries do not exist. Absences of digital libraries in universities have extensively affecting the teaching and learning of faculty members. This study revealed that the faculty members in Universities of Balochistan were found to be familiar with the importance of HEC digital library to some extent, but still the minimum level of usage was evident of its not understanding the significance. There seem some of the genuine issues as like lack of professional and skilled staff to carry out the digital library operations as well as lack of training/programs is dire need in these higher educational institutions of Balochistan.